(untitled) (ENTHYMEMA, 2012)
In this article we reflect on the style the thought of Montaigne’s Essais. In particular we underline the ability of the thinker to attach a new meaning to traditional terms, recovered in unprecedented acceptations. For example, we can find a notion of form that can include multiplicity without force it into the “One”. Montaigne refuses the traditional conception of the form as a rigid essence, as a whole of traits and properties; the “identity of the human subject” – the “humaine condition” – is rather a flexible condition, i.e. open to divergent fates. Montaigne’s thought can therefore be interpreted as a thought of flexibility.